"True" Helicobacter pylori infection and non‐cardia gastric cancer: A pooled analysis within the Stomach Cancer Pooling (StoP) Project. Issue 3 (2nd March 2022) - Morais, Samantha; Costa, Adriana; Albuquerque, Gabriela; Araújo, Natália; Tsugane, Shoichiro; Hidaka, Akihisa; Hamada, Gerson Shigueaki; Ye, Weimin; Plymoth, Amelie; Leja, Marcis; Gasenko, Evita; Zaridze, David; et al.
Abstract: Background: Helicobacter pylori is the most important risk factor for non‐cardia gastric cancer (NCGC); however, the magnitude of the association varies across epidemiological studies. This study aimed to quantify the association between H. pylori infection and NCGC, using different criteria to define infection status. Methods: A pooled analysis of individual‐level H. pylori serology data from eight international studies (1325 NCGC and 3121 controls) from the Stomach Cancer Pooling (StoP) Consortium was performed. Cases and controls with a negative H. pylori infection status were reclassified as positive considering the presence of anti‐Cag A antibodies, gastric atrophy, or advanced stage at diagnosis, as available and applicable. A two‐stage approach was used to pool study‐specific adjusted odds ratios (OR), and 95% confidence intervals (95% CI). A meta‐analysis of published prospective studies assessing H. pylori seropositivity in NCGCs was conducted. Results: The OR for the association between serology‐defined H. pylori and NCGC was 1.45 (95% CI: 0.87–2.42), which increased to 4.79 (95% CI: 2.39–9.60) following the reclassification of negative H. pylori infection. The results were consistent across strata of sociodemographic characteristics, clinical features and lifestyle factors, though significant differences were observed according to geographic region—a stronger association in Asian studies. The pooled risk estimates from the literature were 3.01 (95% CI: 2.22–4.07) for ELISA or EIA and 9.22 (95% CI: 3.12–27.21) for immunoblot or multiplex serology. Conclusion: The NCGC risk estimate from StoP based on the reclassification of H. pylori seronegative individuals is consistent with the risk estimates obtained from the literature. Our classification algorithm may be useful for future studies.